The Effect of Apolipoprotein e4 on Object Mnemonic Discrimination in Healthy Adulthood. (20th December 2022) - Lancaster, Claire L; Daly, Jessica; Berens, Samuel; Tabet, Naji; Dowell, Nicholas; Bakker, Arnold; Bird, Chris; Rusted, Jennifer M
Abstract: Background: Impairment in mnemonic discrimination is a hallmark feature of the very early stages of Alzheimer's Disease (AD) and is associated with aberrant hippocampal function. Carriers of an Apolipoprotein (APOE) e4 gene, the most well‐established risk factor for AD, show differences in hippocampal function from youth. The cognitive consequences of altered brain activation in this group, however, remain poorly understood. Methods: An online web‐platform has been developed – the APOE Memory Bank, which presents a collection of in‐depth behavioural tasks targeting hippocampal (object and spatial mnemonic discrimination) and non‐hippocampal cognitive processes (prospective memory, working memory and executive control). Cognitively healthy adults (aged 45–65 years) were invited to take part from the NIHR BioResource database. Selection processes have ensured a well‐matched, equivalent sample of e4 carriers and non‐carriers. Results: Four hundred and twenty‐one participants have provided data to the APOE Memory bank to date. Ongoing, pre‐registered analyses will test if APOE e4 carriers show alterations in their ability to discriminate objects in memory, and if genotype differences in the cognitive processes supporting successful mnemonic discrimination underpin disparities. The sample is enriched with a high proportion of homozygous e4 carriers, providing a novel examination of gene‐dose effects at scale. Conclusions: Establishing which cognitive processes are sensitive to the detrimental effects of APOE e4 will advance understanding of how genotype differences in brain development confer vulnerability in this high‐risk group. To date, indices of mnemonic discrimination have been used to discriminate preclinical or prodromal AD. This research provides a novel test of whether, in mid‐life, a web‐based object mnemonic discrimination task can differentiate risk for subsequent cognitive impairment. Identifying non‐invasive, easy‐to‐administer risk markers will advance future avenues of prophylactic, personalised intervention